2016
DOI: 10.1021/acs.jpcb.5b11507
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Symmetrization in Glycinium Oxalate under Pressure

Abstract: The study of hydrogen bonds near symmetrization limit at high pressures is of importance to understand proton dynamics in complex bio-geological processes. We report here the evidence of hydrogen bond symmetrization in the simplest amino acid-carboxylic acid complex, glycinium oxalate, at moderate pressures of 8 GPa using in-situ infrared and Raman spectroscopic investigations combined with first-principles simulations. The dynamic proton sharing between semioxalate units results in covalent-like infinite oxal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 93 publications
2
35
0
Order By: Relevance
“…Our high pressure IR and Raman studies have shown a dynamic sharing of the proton between the two semioxalate units of glycinium oxalate, thus mimicking a symmetric hydrogen bond state. These results were corroborated with the help of ab initio calculations which showed that the probability of crossing the midpoint between the oxalates increased with pressure 127 .…”
Section: Organic Molecular Solidssupporting
confidence: 58%
“…Our high pressure IR and Raman studies have shown a dynamic sharing of the proton between the two semioxalate units of glycinium oxalate, thus mimicking a symmetric hydrogen bond state. These results were corroborated with the help of ab initio calculations which showed that the probability of crossing the midpoint between the oxalates increased with pressure 127 .…”
Section: Organic Molecular Solidssupporting
confidence: 58%
“…For example, under compression of the O:H-O bond, the H-O covalent bond becomes longer while the total O–O distance is shortened, leading to the proton centring in the O–O of ice VIII-X phase transition21011121314. The behaviour of the proton is so strange that thermal fluctuation15 and quantum effect of nuclei16 were both considered contributing to the ambiguous behaviour.…”
mentioning
confidence: 99%
“…The crystal structure of BA is built of two parallel sets of dimers and supported by two 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 Thus, the symmetrization of hydrogen bond is expected in BA at higher pressures, which can be found in many compounds containing X-H···X hydrogen bonds. 5,15,[21][22][23] Moreover, the difference of bond length between C-O and C=O as a function of pressure is shown in Figure S5. One can see that the difference of bond length between C-O and C=O is continuous decreasing when pressure is increasing, which indicate the symmetrization of hydrogen bonds will eliminate the distinction between single and double C-O bonds.…”
Section: Resultsmentioning
confidence: 99%
“…A number of investigations on the structural behaviors of hydrogen-bonded molecular crystals under high pressure have been reported. [11][12][13][14][15][16][17][18][19][20] For example, urea experienced four structural changes at 0.48, 0.6, 2.8, and 7.2 GPa, respectively. [17][18] During the phase transitions, large variations were observed in hydrogen bonds, including breakage, formation, and distortion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation